1995
DOI: 10.1002/cjce.5450730116
|View full text |Cite
|
Sign up to set email alerts
|

The solubility of CO2 in a 30 mass percent monoethanolamine solution

Abstract: The solubility of CO2 in a 30 mass % monoethanolamine (MEA) solution has been measured at eight temperatures between 0 and 150°C at partial pressures of CO2 ranging from 0.001 to 20,000 kPa. The data have been correlated using the Deshmukh‐Mather (1981) model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
289
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(323 citation statements)
references
References 15 publications
32
289
1
1
Order By: Relevance
“…6). The capacity of 30 wt% Na 2 CO 3 at equilibrium with flue gas with 0.1 bar CO 2 partial pressure allowing for the precipitation of NaHCO 3 (s) calculated to be 0.10 g CO 2 per gram solvent, as determined by Pitzer's equations and GWB Software (see Supplementary Methods) 27 , the same as MEA 28 . On the basis of previous analysis, the working capacity of sodium carbonate solution is slightly higher than MEA (7.1 versus 6.9% g per gram) 29,30 , but the values depend on process conditions.…”
Section: Resultsmentioning
confidence: 99%
“…6). The capacity of 30 wt% Na 2 CO 3 at equilibrium with flue gas with 0.1 bar CO 2 partial pressure allowing for the precipitation of NaHCO 3 (s) calculated to be 0.10 g CO 2 per gram solvent, as determined by Pitzer's equations and GWB Software (see Supplementary Methods) 27 , the same as MEA 28 . On the basis of previous analysis, the working capacity of sodium carbonate solution is slightly higher than MEA (7.1 versus 6.9% g per gram) 29,30 , but the values depend on process conditions.…”
Section: Resultsmentioning
confidence: 99%
“…CO 2 solubility measurements for loaded MEA obtained from the FTIR technique are compared to those reported by Jou et al (1995) and Dugas (2009) (2008) were obtained using the FTIR analysis. Dugas (2009) measured CO 2 solubility using a wetted wall column whereas Ermatchkov (2006) measured the equilibrium partial pressure using headspace gas chromatography.…”
Section: Mea-co 2 -H 2 O Benchmarkingmentioning
confidence: 95%
“…A number of previous studies have reported some cost and/or performance data for specific amine-based systems, including hypothetical applications to coal-fired power plants (19)(20)(21)(22)(23).…”
Section: Scope Of This Studymentioning
confidence: 99%
“…It was developed over 60 years ago as a general, non-selective solvent to remove acidic gas impurities (e.g. H 2 S, CO 2 ) from natural gas streams (21). The process was then adapted to treat flue gas streams for CO 2 capture.…”
Section: Overview Of Amine-based Co 2 Capture Systemsmentioning
confidence: 99%